Effect of electromigration on interfacial reactions between electroless Ni-P and Sn–3.5% Ag solder - Kumar, A. (2012)
Effect of electromigration on interfacial reactions between electroless Ni–P (EL-Ni) and eutectic Sn–3.5% Ag solder has been investigated. Sandwich-type reaction couples, Cu/EL-Ni/Sn–3.5% Ag/EL-Ni/Cu, having two EL-Ni/Sn–3.5% Ag interfaces were prepared with the help of reflow process. During reflow, Ni3Sn4 intermetallic formed at the EL-Ni/Sn–3.5% Ag interfaces with a dark thin Ni3P layer underneath it. The reaction couples were annealed at 160 and 180 °C for various durations with and without the passage of DC current of 1×103 A/cm2 density. It was found that current does not affect the stoichiometry of the intermetallics formed at the EL-Ni/Sn–3.5% Ag interfaces. The same Ni3Sn4 intermetallic formed in the samples annealed at both the temperatures with and without current. Formation of Kirkendall voids in the Ni3P layer showed that Ni diffuses from EL-Ni through the grain boundaries of Ni3P to form Ni3Sn4. It was observed that current retards the Ni3Sn4 growth at both the anode and cathode side interfaces at 180 °C, while no significant retardation was observed at 160 °C. This effect of electromigration on the EL-Ni/Sn–3.5% Ag interfacial reactions was due to the presence of Ni3P layer in between EL-Ni and Ni3Sn4.